2018
DOI: 10.1093/jnen/nlx118
|View full text |Cite|
|
Sign up to set email alerts
|

Pediatric Chordomas: Results of a Multicentric Study of 40 Children and Proposal for a Histopathological Prognostic Grading System and New Therapeutic Strategies

Abstract: Pediatric chordomas are rare malignant neoplasms, and few data are available for optimizing therapeutic strategies and outcome. This study aimed at evaluating how best to manage them and to identify prognostic factors. This multicentric retrospective study included 40 children diagnosed with chordomas between 1966 and 2012. Clinical, radiological, and histopathological data, treatment modalities, and outcomes were reviewed. The median age was 12 years old. Most chordomas were histologically classical forms (45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 52 publications
3
19
0
Order By: Relevance
“…We found no signi cant difference, which is consistent with several studies [32,2]. Several previous studies showed that dural penetration [37,7] and age [29,5] were associated with long-term outcomes, and we demonstrated that they were not independent risk factors after multivariate analysis [23,36].…”
Section: Other Risk Factors For Outcomesupporting
confidence: 92%
“…We found no signi cant difference, which is consistent with several studies [32,2]. Several previous studies showed that dural penetration [37,7] and age [29,5] were associated with long-term outcomes, and we demonstrated that they were not independent risk factors after multivariate analysis [23,36].…”
Section: Other Risk Factors For Outcomesupporting
confidence: 92%
“…Chordomas represent approximately 0.2% of primary brain tumours 227 . The cumulative incidence is 1:1,000,000, with different sex predominance among the series 227‐229,233‐241 . Chordomas usually occur in Caucasian 228,229 adults between the ages of 30 and 70 years.…”
Section: Clival Chordomamentioning
confidence: 99%
“…Chordomas usually occur in Caucasian 228,229 adults between the ages of 30 and 70 years. Less than 5% appear in the first two decades of life 17 (average age around 10 years) 235,241 . Compared to the adult counterpart, the majority of the paediatric chordomas are primarily found intracranially, mainly in the spheno‐occipital synchondrosis of the clivus, 228,229,233,242 although it has been described in other sites including the sellar and parasellar region, as well as the sphenoid sinus, amongst others 17,228,243,244 …”
Section: Clival Chordomamentioning
confidence: 99%
See 1 more Smart Citation
“…The INI‐1‐negative chordomas differ from classic chordomas also by the absence of further cytogenetic aberrations such as chromosome 9 or chromosome 10 deletions, which are commonly observed in classic chordomas [89]. In line with the evidence from other INI1 deleted tumour entities, INI‐1‐deficient chordomas seem to have a particularly bad prognosis [90]. The immunohistochemical absence of INI‐1 thus prompts the question if these tumours are susceptible to the same therapeutic approaches as ATRT such as, for example, EZH2 inhibition, which have been studied widely in MRT.…”
Section: Smarcb1 Alterations In Paediatric Brain Tumoursmentioning
confidence: 99%